2022
DOI: 10.3389/fmicb.2022.948875
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial communities response to different fertilization regimes in young Catalpa bungei plantation

Abstract: Fertilization is a fundamental aspect of global forest management that enhances forest productivity and drastically affects soil microbial communities. However, few studies have investigated the differences and similarities in the responses of below-ground microbial communities to different fertilization schemes. The effects of fertilization regimes on the composition and diversity of soil fungal and bacterial communities were investigated in a young Catalpa bungei plantation in Shandong Province, Eastern Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Previous research has shown that appropriate fertilization levels promote the proliferation of soil bacteria, fungi, and actinomycetes, mainly due to the nitrogen, phosphorus, and potassium provided by inorganic fertilizers, which serve as important nutrient sources for the growth and reproduction of soil microorganisms [5,35]. However, excessive fertilization led to a reduction in bacterial activity and diversity [35], consistent with our findings. Other studies have indicated that with increasing nitrogen application, the fungal biomass decreased while the bacterial biomass remained relatively stable [36,37], which differed from our research results.…”
Section: Effects Of Inorganic Fertilizer Level and Coffee Husk Return...supporting
confidence: 90%
See 1 more Smart Citation
“…Previous research has shown that appropriate fertilization levels promote the proliferation of soil bacteria, fungi, and actinomycetes, mainly due to the nitrogen, phosphorus, and potassium provided by inorganic fertilizers, which serve as important nutrient sources for the growth and reproduction of soil microorganisms [5,35]. However, excessive fertilization led to a reduction in bacterial activity and diversity [35], consistent with our findings. Other studies have indicated that with increasing nitrogen application, the fungal biomass decreased while the bacterial biomass remained relatively stable [36,37], which differed from our research results.…”
Section: Effects Of Inorganic Fertilizer Level and Coffee Husk Return...supporting
confidence: 90%
“…Soil microorganisms play a vital role in soil structure formation as well as organic matter and mineral decomposition [34]. Previous research has shown that appropriate fertilization levels promote the proliferation of soil bacteria, fungi, and actinomycetes, mainly due to the nitrogen, phosphorus, and potassium provided by inorganic fertilizers, which serve as important nutrient sources for the growth and reproduction of soil microorganisms [5,35]. However, excessive fertilization led to a reduction in bacterial activity and diversity [35], consistent with our findings.…”
Section: Effects Of Inorganic Fertilizer Level and Coffee Husk Return...mentioning
confidence: 99%
“…The activity of soil urease (S-UE) was determined by the indophenol blue colorimetric method. Whereas the activities of soil acid phosphatase (S-ACP), soil catalase (S-CAT), and soil sucrase (S-SC) were determined by the colorimetric method ( Guan et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This observed difference in diversity can be attributed to the larger amount of rainfall experienced during the rainy season, which created a more favorable habitat for microorganisms [29]. One factor contributing to the alteration in fungal community structure is depth; as the soil depth changes, so do soil nutrient levels, causing alterations to the soil fungal community [30]. The study of Bainard revealed that differences in the AMF community were caused by environmental parameters such as soil phosphate concentration, water content, and the type of host plant [31].…”
Section: Response Of Amf Communities To Seasonal Changesmentioning
confidence: 99%